Effectiveness of Legal Aid Services in Joint Property Cases in Marriage at Partner Legal Aid Institutions Madani West Sulawesi - Wawan (IAIN Parepare, 2023)
This study aims to analyze the problem of free legal aid for the weak and poor. This provision is regulated in the Legal Aid Law, which is the embodiment of Article 27 paragraph (1) and article 28D paragraph (1) which shows that everyone has an equal position before the law and is entitled to legal protection. The state has juridically arranged in such a way, so that justice can be felt by all levels of society, but the application of the law is still far from justice itself. This research is empirical legal research using a sociological juridical approach, which is an approach that emphasizes research that aims to obtain legal knowledge empirically. The results showed that LBH Mitra Madani as a structural institution, has provided legal assistance in litigation and non-litigation. In addition, LBH Mitra Madani also conducts legal counseling, community organizing, and training in the field of law. However, the obstacle is the absence of financial support from the government, because LBH Mitra Madani has not been accredited. The cases that have been accompanied from 2019 to 2022 amounted to 37 cases, where the cases handled by LBH Mitra Madani were dominated by civil cases. The obstacles of LBH Mitra Madani in providing legal assistance are legal substance and legal structure. By regulation, legal assistance provided by LBH Mitra Madani to the poor should be free. However, in fact, LBH Mitra Madani still collects fees from every client who is given legal assistance, this is because LBH Mitra Madani has not received financial assistance from the Government. In addition to substantial factors that are obstacles to the effectiveness of LBH Mitra Madani in providing legal assistance are legal structure factors, which include law enforcement institutions (police, prosecutors, courts and advocates).